Análisis experimental de la curva de Laffer y la evasión fiscal en Bolivia - Francisco Javier Aliaga; Anna Oropeza Farel; Javier von Borries (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2015)
– Tax evasion is an illegal activity combated by the tax administration through different tools. Implicitly the risk is present in this type of activity. Therefore, the risk assessment is an important component on the decision of evasive behavior. At the same time, there are other factors that determine the adoption of this behavior. The question lies on knowing what tax incentives and what policies can be useful for better monitoring and control. This document uses experimental field methodology to investigate the complex behavior of taxpayers on the issue of tax evasion. The aim of making changes in the structure of incentives, such as income, the probability of inspection and variations in the tax rate, is evaluate the behavior of economic agents when these changes are made. The experiment results indicate that an important factor is the risk aversion in the adoption of tax evasion behavior, but that the determining factor when paying taxes is the income of individuals: a higher income, greater tax compliance. We also found that the greater the chance of being audited and higher fines, increased compliance in paying taxes.
Keywords: C91; H31; 330